Antifungal and Plant Growth Promoting Activities of Indigenous Rhizobacteria Isolated from Maize (Zea mays L.) Rhizosphere. Issue 1 (2nd January 2018) - Bjelić, Dragana; Marinković, Jelena; Tintor, Branislava; Mrkovački, Nastasija
ABSTRACT: Plant growth promoting rhizobacteria (PGPR) enhance the plant growth directly by assisting in nutrient acquisition and modulating plant hormone levels, or indirectly by decreasing the inhibitory effects of various pathogens. The aim of this study was to select effective PGPR from a series of indigenous bacterial isolates by plant growth promotion and antifungal activity assays. This study confirmed that most of the isolates from maize rhizosphere were positive for PGPR properties by in vitro tests. Azotobacter and Bacillus isolates were better phosphate solubilizers and producers of lytic enzymes, hydrocyanic acid (HCN), and siderophores than Pseudomonas . Production of indole-3-acetic acid (IAA) and antifungal activity were the highest in Azotobacter, followed by Bacillus and Pseudomonas . The most effective Azotobacter isolates ( Azt3, Azt6, Azt12 ) and Bacillus isolates ( Bac10, Bac16 ) could be used as PGPR agents for improving maize productivity. Further selection of isolates will be necessary to determine their efficiency in different soils.